Análisis de la existencia de vulneración de derecho al buen vivir en adultos mayores - Carrillo Solís, Heyddy Francis (2025)
This research analyzes the violation of one of the fundamental rights that all human beings possess, including the elderly: the right to a good quality of life, which is one of the rights established in the Constitution. Additionally, it seeks to identify the causes of the violation of the right to a good quality of life for the elderly, emphasizing the responsibility of both the State and the family in protecting the rights of this group, which is considered vulnerable by the Constitution of the Republic of Ecuador and other national and international regulations..........